Hydrogen sulfide regulates hippocampal neuron excitability via S-sulfhydration of Kv2.1 - Dallas, Mark L. (Sci Rep, 2021)
Hydrogen sulfide (H(2)S) is gaining interest as a mammalian signalling molecule with wide ranging effects. S-sulfhydration is one mechanism that is emerging as a key post translational modification through which H(2)S acts. Ion channels and neuronal receptors are key target proteins for S-sulfhydration and this can influence a range of neuronal functions. Voltage-gated K(+) channels, including Kv2.1, are fundamental components of neuronal excitability. Here, we show that both recombinant and native rat Kv2.1 channels are inhibited by the H(2)S donors, NaHS and GYY4137. Biochemical investigations revealed that NaHS treatment leads to S-sulfhydration of the full length wild type Kv2.1 protein which was absent (as was functional regulation by H(2)S) in the C73A mutant form of the channel. Functional experiments utilising primary rat hippocampal neurons indicated that NaHS augments action potential firing and thereby increases neuronal excitability. These studies highlight an important role for H(2)S in shaping cellular excitability through S-sulfhydration of Kv2.1 at C73 within the central nervous system.